endovascular repair of an isolated iliac artery aneurysm in a patient with liver cirrhosis - Tahooni, Azadeh; Vahedinezhad, Milad (International Journal of Cardiovascular Practice)
Endovascular repair is increasingly becoming the main strategy for management of aortic and peripheral aneurysms. Several methods have been chosen to treat aneurysms based on the anatomy, coexisting nearby aneurysms and available tools. We present a 60 years old man with an isolated large iliac artery aneurysm which discovered incidentally and was treated using an endovascular approach and obliterating internal iliac artery without early and late complications at 3 years long follow up.